Affective conflict and identification of knowledge sources in MNE teams. Issue 5 (October 2017) - Vahtera, Pekka; Buckley, Peter; Aliyev, Murod
Highlights: We examine affective conflict and identification of knowledge sources in MNE teams. We consider two types of interpersonal conflict: relational tension and self-interest. We further analysed potential moderation of geographic and nationality differences. Our hypotheses were tested with 1181 dyads within 40 MNE teams. Affective conflict negatively influences identification of knowledge, and geography and nationality moderate the link between conflict and knowledge. Abstract: How does affective conflict influence identification of knowledge sources in MNE teams? We apply social exchange theory and consider the effect of two types of affective interpersonal conflict: relational tension and self-interest on identification of knowledge sources in MNE teams. We further analyse how these effects are related to geographic and nationality differences. We test our hypotheses with a field study of 1181 dyadic interactions between 160 members within 40 MNE teams engaged in product innovation, human resources, and operational improvement in three large diversified MNEs. We find that affective conflict has a direct negative relationship to identification of knowledge sources in MNE teams. This relationship is further negatively moderated by geographic differences and nationality differences. Our study contributes to theoretical and empirical micro-foundations of conflict and identification of knowledge sources in MNE teams.